Psychological Assessments for the Partially Edentulous Persons through Different Scales, According to Some Demographical Variables. - Monia MN Kandil (University of Mosul, College of Dentistry, 2008)
Aims: To get more information about the psychological condition for the partially edentulous persons, and the effect of culture and other demographical factors on there psychological condition. Materials and Methods: Fifty persons were diagnosed and were suitable for the criteria of the study, only 38 of them continued until completing the questionnaires; Information about members that needed for the study were taken. Mainly the sample group was divided to Iraqi and Egyptian sample, then sub grouped according to sex, age, education, financial and anxiety levels; Each member at this study requested to 3 method of psychological assessments, which were: Eysenck Personality Inventory; Hamilton Anxiety Scale; And Mental Health Test, then the scales results included in statistical analysis, by using the General Linear Models and Duncan's Multiple Range Analysis. Results: For the Iraqi group,a significant difference with Euphoria Scale related to age group variable, and with Hamilton Anxiety Scale related to sex variation, as well as anxiety level differences. For Egyptian group, the results showed significant differences with Neuroticism, Hamilton Anxiety Scales with anxiety levels differences; Also with Mental Health Scale related to all demographic variables taken at this study, except with the educational variation. Duncan's Multiple Range Test for partially Iraqis' and Egyptians' groups according to sex, education, finances, age and anxiety variation; Different significant values appeared at each one except with Euphoria Scale and some variables. Conclusions: There were significant differences in all psychological traits that examined at this study, except with Euphoria Scale. The Egyptians generally tend to be more euphoric, neurotic, anxious and less in mental health than Iraqis. The Lying and anxiety scales had a reverse relationship with the education and financial variation. Usually an anxious person tends to be more neurotic and less in mental health abilities; Usually females had more anxiety tendency than males.